Vulnerabilidad administrativa del Estado hondureño en situaciones de emergencia con la habilitación de las contrataciones directas durante la pandemia del COVID -19 - Paz Macias, Jenssy Carolina (Universidad Nacional del Litoral, 2020)
This research presents a legal analysis from the view of administrative law related to acts carried out by public officials in application of the current regulations regarding the state of emergency, whose experience has revealed the administrative vulnerability of Honduras in  direct  procurement in which inexperience is visible, deficiency in fiscal controls before and during procurement, as well as legal negligence of law-appointed actors who must act in the processes of approval and disbursement of national capital, observing actions subsequent to direct procurement that facilitated non-compliance with fiscal control, which have generated confusion and questions on the public agenda, considering a multimillion-dollar investment, insecure, doubtful with the lack of visible guarantees of insurance of funds paid to third parties. Legal analysis involves the identification and description of the weaknesses of the current Honduran regulations and the recommendations for its reform and creation of complementary special laws, which guarantee the Honduran people a better management of financial resources against phenomena of the magnitude of the effects of the Covid-19 pandemic.